Pengaruh Metode Pembelajaran Kooperatif Model Numbered Heads Together dalam Meningkatkan Prestasi Belajar PPKN pada Siswa Kelas VIII SMP NEGERI 42 Surabaya - nunuk pariantie (ASANKA : Journal of Social Science and Education, 2022)
Professional teachers should be able to overcome these problems. There are many learning models that can be chosen to increase students' creativity and responsibility. One of the learning models that can be used is the Cooperative Numbered Heads Together where students are required to work together and be responsible until the end of the lesson. The purpose of this research is to increase student activity in Civics learning. The type of research used is quantitative. Data collection tools used are observation sheets, field notes, and questionnaires. The results showed that there was an increase in learning achievement in Civics subjects, an increase of 80% of students who passed the competency test for class VIII-E an increase of 80%, class VIII-F by 80% and class VIII-G by 82.85%. Based on the multiple R value, which is 0.899, which means the relationship between the independent and dependent variables can be said to be very strong (close to 1). So that the cooperative learning approach (X) has a very strong relationship with learning achievement in students of SMP Negeri 42 Surabaya.